An effective integrated system used in separating for anaerobic digestate and concentrating for biogas slurry. Issue 28 (19th December 2021) - Bao, Yali; Fu, Yanyan; Wang, Caixia; Wang, Hong
ABSTRACT: In this work, an integrated system was developed which achieves full-scale separation and valorization for anaerobic digestate of livestock manure, completes anaerobic digestate separation, biogas residue recovery, biogas slurry concentration and water recovery simultaneously. Compared with the centrifugal pretreatment, the particle size of the biogas slurry is reduced significantly via P/I pretreatment, the liquid recovery ratio is increased to 94.0%, this leads to the substantial increase of the entire system nutrients recovery ratio directly. What's even more valuable is the permeate flux of UF membrane is increased for 2.5 times via P/I pretreatment. The results showed that P/I pretreatment had much better effects in solid-liquid separation of biogas slurry, which reduced the load of the subsequent membrane separation unit and enhanced the UF membrane permeation flux greatly. That prolonged the cleaning cycle and service life of the UF membrane. The efficiency of system was validated according to the nutrients recovery ratios, the biogas slurry concentration efficiency, the recovery of water and the pollutants levels of discharged water. The results showed that the total nutrients recovery ratio was about 100%, the concentration ratios of biogas slurry were more than 3.7 (via UF) and 6.6 (via RO), total water recovery ratio was 46.9% (ratio of the discharged water volume to the digestate volume, the COD removal ratio of the discharged water was 99.9%, the contents of COD, TP and TN were 43.6 mg/L, 0.2 mg/L and 1.2 mg/L, which reached the nation integrated wastewater discharged standard class I. GRAPHICAL ABSTRACT: UF0001